[About CEU - Interviews]
The first part of the tape contains three interviews. The first interview is with the President and Rector of the CEU, Josef Jařab. The second is with Academic Pro-Rector of CEU Sorin Antohi and the third with Prof. William Newton-Smith (Member of CEU Board of Trustees, Board Member of the Roma Educational Fund, and Professor at Oxford University). They answer questions related to the history of the CEU, the emergence of the idea of a Western university model in Central and Eastern Europe, the purpose of the university and its role in Central and Eastern Europe.